The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpls.2022.829381
|View full text |Cite
|
Sign up to set email alerts
|

Differentiate Responses of Soil Microbial Community and Enzyme Activities to Nitrogen and Phosphorus Addition Rates in an Alpine Meadow

Abstract: Nitrogen (N) and phosphorus (P) are the dominant limiting nutrients in alpine meadows, but it is relatively unclear how they affect the soil microbial community and whether their effects are rate dependent. Here, N and P addition rates (0, 10, 20, and 30 g m–2 year–1) were evaluated in an alpine meadow and variables related to plants and soils were measured to determine the processes affecting soil microbial community and enzyme activities. Our results showed that soil microbial biomass, including bacteria, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 109 publications
6
12
0
Order By: Relevance
“…Conversely, P fertilization could alleviate microbial P limitation and increase microbial N limitation. SEM showed that P fertilization affected soil bacterial community composition through increased P availability (Figure 8b), which might alleviate plant P limitation (Zi et al, 2022).…”
Section: Correlations Of Bacterial Community Structure With Abiotic A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, P fertilization could alleviate microbial P limitation and increase microbial N limitation. SEM showed that P fertilization affected soil bacterial community composition through increased P availability (Figure 8b), which might alleviate plant P limitation (Zi et al, 2022).…”
Section: Correlations Of Bacterial Community Structure With Abiotic A...mentioning
confidence: 99%
“…We aimed to (1) determine the responses of soil bacterial community diversity and structure to varying rates of N and P fertilization, and (2) explore the main abiotic and biotic factors structuring soil bacterial communities. Based on previous studies, we hypothesized that (1) high levels of N fertilization would decrease soil bacterial diversity because of a decline in soil pH by N fertilization, whereas P fertilization would have few impacts (Wang, Liu, et al, 2018; Yan et al, 2022); (2) the effect of N, P, and NP fertilization on the bacterial community composition would be rate‐dependent because multi‐level fertilization creates a gradient of soil nutrient availability (Liu, Jiang, et al, 2020; Zi et al, 2022); and (3) based on the nutrient limitation theory, the different soil and plant factors that drive soil bacterial community diversity and composition could greatly differ under N, P, and NP fertilization (Elser et al, 2009; Ma et al, 2019; Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) enrichment can increase soil P bioavailability and accelerate N uptake by plants, which can increase plant biomass and change the structure of plant communities ( Ren et al, 2017 ; Xiao et al, 2020 ). This reshaping of the composition of plant communities through nutrient enrichment can change the animal and microbial diversity and abundance above and below ground ( Liu et al, 2021 ; Villa-Galaviz et al, 2021 ; Zi et al, 2022 ), in addition to potentially altering biodiversity at multiple trophic levels within the community’s food webs ( Tylianakis et al, 2008 ; Burkle and Irwin, 2009 ; Xiao et al, 2020 ; Villa-Galaviz et al, 2021 ). Some studies on the responses of pollinator communities and plant–pollinator interaction networks to nutrient supply in grassland ecosystems have been conducted, but their results have been inconsistent ( Burkle and Irwin, 2009 ; Carvalheiro et al, 2019 ; Villa-Galaviz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that adding N and P can increase the net primary productivity of grasses, while predominantly reducing the biomass and abundance of legumes on the alpine grasslands ( Ren et al, 2016 ; Ren et al, 2017 ; Luo et al, 2019 ). Many recent studies have focused on the effects of N and P addition on plants and soil microorganisms in the alpine grasslands ( Zong and Shi, 2019 ; Liu et al, 2021 ; Dong et al, 2022 ; Zi et al, 2022 ), showing that combined N and P enrichment decreased the diversity of plants but increased net primary productivity ( Ceulemans et al, 2013 ; Xiao et al, 2020 ). However, because bottom-up effects driven by changes in flowering plant diversity and flower abundance could have a major impact on the plant–pollinator interactions, few studies have focused on how changes in plant community structure due to N and P enrichment affect the richness and abundance of pollinators in this alpine grassland ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, extreme drought can affect Re and Rs by altering plant and soil extracellular enzyme activities in alpine wetland ( Yan et al., 2021 ). In alpine meadow, N and P addition significantly affect t plant communities ( Ma et al., 2021 ), soil microbial community and enzyme activities ( Zi et al., 2022 ), and microbial functional genes ( Xiao et al., 2022 ). In alpine steppe, N and P application led to an increase in aboveground biomass ( Li et al., 2021b ), and increased intensity of bacteria and fungi ( Li et al., 2021c ), also affected the plant functional traits ( Li et al., 2022d ).…”
mentioning
confidence: 99%